Dance for sports a practical guide - Apostolos, Margo K. (Oxford University Press, 2019)
In Dance for Sports, author, teacher, dancer, athlete, and researcher Margo K. Apostolos offers a new training approach for athletes and coaches that synthesizes common techniques between athletics and dance. by utilizing this approach, in- and off-season athletes can improve efficiency and technique. Based upon the author's decades-long career and extensive experience with athletes and coaches in a variety of sports such as football, basketball, swimming, tennis, track and field, and more, Dance for Sports is a fully integrative guide for students and instructors alike